The Politics of Social Protest : Comparative Perspectives on States and Social Movements - Klandermans, Bert; Jenkins, J. Craig, 1948- (Book collections on Project MUSE., 1995)
Bringing together celebrated scholars from diverse traditions and backgrounds, this volume focuses on the reciprocal relationships among social movements, states, and political parties. The essays are organized around three key questions: Why do citizens resort to the often risky and demanding strategy of using disruptive protest when other channels of political intervention appear to be available? What is the relationship between social protest movements and systems of political representation? And what is the impact of the structure and development of the state on social movements themselves.